If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8x + -9 = 4x Reorder the terms: -9 + 8x = 4x Solving -9 + 8x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -9 + 8x + -4x = 4x + -4x Combine like terms: 8x + -4x = 4x -9 + 4x = 4x + -4x Combine like terms: 4x + -4x = 0 -9 + 4x = 0 Add '9' to each side of the equation. -9 + 9 + 4x = 0 + 9 Combine like terms: -9 + 9 = 0 0 + 4x = 0 + 9 4x = 0 + 9 Combine like terms: 0 + 9 = 9 4x = 9 Divide each side by '4'. x = 2.25 Simplifying x = 2.25
| 3(2X+2)-4(3X+2)=5X+20 | | (6x-3)=(4x+7) | | 2x=(360+2) | | (6)*(3x+2)=(6)*(5x-10) | | R(6x-3)=(4x+7) | | 5n-2(n-2)=-11+3n+5 | | 4y+2=8(y+7) | | 5(-9+x)=-25 | | 6(2+x)=72 | | -2x-30=28-4x | | (3)*(2x+9)=27 | | -8u-30=-6(u+7) | | -3rs(2r^2s+12t-7)= | | -2x-66=62-10x | | 4(x-7)=7x-13 | | K-15=-40 | | -55-2x=-5x+17 | | -5(1+4x)=195 | | 2n+8=3(n-9) | | 3y+18=-6(y-9) | | -31-7x=17-11x | | -3x+5(-9+4x)=-x-4 | | (4)*(3x+12)=64 | | -76+7x=104-2x | | 12x-25=7x+35 | | -4x-14=-7x+12 | | 5x-2(-2x+19)=-83 | | 3(1x+5)=42 | | 8x-68=77+4x | | 3x-6(1+x)=-9x+9 | | 3b-50=4b-74 | | -124+12x=5x+86 |